The role of Ulmus laevis in German floodplain landscapes - Mackenthun, G.L.
(Es, En)
ilus., 48 ref.
Keywords: ULMUS; ENFERMEDADES DE LAS PLANTAS; BOSQUES; OPHIOSTOMA; HONGOS; ESPAÑA; OLMO; BOSQUE DE RIBERA; HEMEROBIS; GRAFIOSIS